Magnetic Nature of the CrIII–LnIII Interactions in [CrIII2LnIII3] Clusters with Slow Magnetic Relaxation. Issue 2 (2nd February 2018) - Zhao, Xiao‐Qing; Xiang, Shuo; Wang, Jin; Bao, Dong‐Xu; Li, Yun‐Chun
Abstract: Two 3 d ‐4 f hetero‐metal pentanuclear complexes with the formula [Cr III 2 Ln III 3 L10 (OH)6 (H2 O)2 ]Et3 NH [Ln=Tb (1 ), Dy (2 ); HL=pivalic acid, Et3 N=triethylamine] have been produced. The metal core of each cluster is made up of a trigonal bipyramid with three Ln III ions (plane) and two Cr III ions (above and below) held together by six μ 3 ‐OH bridges. Also reported with this series is the diamagnetic Cr III –Y III analogue (3 ). Fortunately, we successfully prepared Al III –Ln III analogues with the formula [Al III 2 Ln III 3 L10 (OH)6 (H2 O)2 ]Et3 NH⋅H2 O [Ln=Tb (4 ), Dy (5 )], containing diamagnetic Al III ions, which can be used to evaluate the Cr III –Ln III magnetic nature through a diamagnetic substitution method. Subsequently, static (dc) magnetic susceptibility studies reveal dominant ferromagnetic interactions between Cr III and Ln III ions. Dynamic (ac) magnetic susceptibility studies show frequency‐dependent out‐of‐phase ( χ ′′) signals for [Cr III 2 Tb III 3 ] (1 ), [Cr III 2 Dy III 3 ] (2 ), and [Al III 2 Dy III 3 ] (5 ), which are derived from the single‐ion behavior of Ln III ions and/or the Cr III –Ln III ferromagnetic interactions. Abstract : Time to relax : Two 3 d –4 f pentanuclear [Cr2 Ln3 ] complexes and the diamagnetic "blanks", [Cr2 Y3 ] and Al2 Ln3, are synthesized. [Cr2 Tb3 ] and [Cr2 Dy3 ] display strong ferromagnetic interactions between Cr III and Ln III ions, and [Cr2 Tb3 ], [Cr2 Dy3 ], and [Al2 Dy3 ] exhibit slow magnetic relaxation.